Revisiting the practice of Bible-translation : the need to engage ordinary believers when translating the Psalms: original research - Dickie, June F. (Verbum et Ecclesia, 2018)
Many young isiZulu speakers find the 1959 Bible translation difficult to read and understand. However, they are interested in getting inside the black box of Bible translation, and being participants in the process. Moreover, they have a culture of composing and performing poetry, which lends itself to their involvement in the translation and performance of biblical poetry. An experimental study sought to see if Zulu youth could compose translations of some praise psalms and perform them such that the community would accept them as ‘biblical material’, and relevant and engaging for young people. The methodology was to invite interested persons to participate in workshops that provided basic training in Bible translation, features of oral communication and performance, Zulu and biblical poetry and Zulu music. The participants then made their own translations of some short psalms, and performed them as songs, rap or spoken poetry items. The results suggest several benefits that could be replicated in other situations and with other language groups. These include new, vibrant ways to share Scripture, and a means for individuals to engage with the Scriptures and ‘own’ the translation. In conclusion, there is an open door for ‘ordinary’ members of the community (especially those interested in poetry and music) to contribute significantly to poeticallybeautiful and rhetorically-powerful translations of biblical psalms. Moreover, the experience they gain will not only support the discipleship ministry of the church, but also its outreach to other young people, drawing them in by engaging and relevant performances of the biblical message. Intradisciplinary and/or interdisciplinary implications: This study challenges the traditional perspectives of Bible translation and Practical Theology, suggesting that ‘ordinary’ members of the community can enrich the translation of biblical poetry, and their engagement in the process can have many positive outcomes in terms of church ministry.
free